Fronteiras e paradoxos: a relação intermidiática entre cinema e performance no documentário Espaço além - Marina Abramović e o Brasil - Balász, Huli de Paula (2020)
This work analyzes the Brazilian documentary Espaço além - Marina Abramović and Brazil (The Space In Between: Marina Abramović and Brazil, Marco Del Fiol, 2016) for the bias of intermediality. The film approaches Abramović's trajectory in seek of healing and inspiration around the country. In her pilgrimage, the artist travels through regions of Brazil experiencing sacred rituals and exploring the boundaries between art, immateriality and consciousness. As theoretical reference, Ágnes Pethő’s (2018) concept of “in-betweenness” is considered and supported by the intermediality research axis also based on authors such as Dick Higgins (2012) and Irina Rajewsky (2012). The aim of this research is to investigate how the intermedial relationship between cinema and performance in that film reveals the subjective dimension of the character. In this regard, it also studies concepts of performance in authors such as Richard Schechner (2006), Roselee Goldberg (2016) and Tania Alice (2014). Besides, this research verifies possible comparison between the mode of performative documentary (Bill Nichols, 2012) and remediation (Jay David Bolter and Richard Grusin, 1999) of performance in film, since one can notice the displacement of the performance to the cinematographic universe throughout Abramović’s journey.